Večstavčna skladnja pri pouku italijanščine - Mertelj, Darja (Vestnik za tuje jezike, 2013)
When teaching Italian as a foreign language, learners insecurities about using conjunctions and tenses in subordinate clauses can be noticed very early. Temporality, relative temporality and modality are signalled by Italian verb forms which function in a largely different (or apparently similar) way in comparison to Slovene. If true similarities can be exploited in the process of teaching/learning by means of a positive transfer, apparent similarities and differences between the two language systems should, on the other hand, be clarified to avoid negative transfer (interference). During the whole learning process language awareness should be developed, also through contrastive insights into the linguistic systems concerned. Taking as a starting point a text suitable for level B1, some problematic points are presented, for which a series of tasks can be suggested with the aim of helping the learner master complex clause syntax and develop language awareness.
Keywords: Italian; italijanščina; tuji jeziki; tuji/drugi jezik; skladnja; syntax; sintaksa; jezikovni pouk; didactic method; didaktika; metodika